KARAKTERISTIK BRIKET DARI ARANG DAUN KELAPA SAWIT DAN ARANG CANGKANG BIJI KARET DENGAN PEREKAT TAPIOKA - Bema, Eykel Sura; Hamzah, Faizah; Zalfiatri, Yelmira (SAGU, 2021)
This research aims to get the best characteristics of charcoal briquette palm leaves and rubber seed shells in making briquettes with tapioca. The study was conducted experimentally using a Complete Randomized Design (CRD) with five treatments and three replications to get 15 experimental units. The treatments in this study were the ratio of palm oil leaves charcoal and rubber seed shells charcoal namely: DC1 (50:50), DC2 (40:60), DC3 (30:70), DC4 (20:80) and DC5 (10:90). Data were statistically analyzed using Analysis of Variance (ANOVA) follow add Duncan’s Multiple Range Test (DMRT) at 5% level. The parameters observed were density, compressive strength, moisture content, vapor content, ash content, bound carbon content, and heating value. The results of palm oil charcoal leaves and rubber shells charcoal with tapioca adhesive have a significant effect on density, compressive strength, water content, vapor content, ash content, bound carbon content and heating value. Based on the analysis results, the best treatment in this study was DC5 (10:90) with a water content of 4.85%, density of 0.56 g/cm3, compressive strength of 0.48 kg/cm2, ash content of 3.43%, evaporating content of 11.68%, bound carbon content of 80.12%, and heating value of 7,504.59 cal/g.